A educação diferenciada para o fortalecimento da identidade quilombola: estudo nas comunidades remanescentes de quilombos do Vale do Ribeira - Silva, Elson Alves da (2011)
This study aimed to explore the process of deploying a Differentiated Education in the State School Quilombola EEMaria Princess Antonia Pimps in Vale do Ribeira-SP city of Eldorado. The school serves a population of approximately 420 students distributed between Early Childhood Education, Elementary and High School who live in six maroon communities around them. The school was founded in 2004 and is an achievement of Quilombo Ivaporunduva, San Pedro, Galvao, Nhungura, Sapatu and Andre Lopes, and this is the community where the school is located. The study first addresses the struggle waged by the leaders maroon over six years for establishment / founding the first school to quilombos in the Vale do Ribeira. Examines the struggles of leadership with representatives from the Education Department in Eldorado, requiring a different school for the care of children and young maroon communities. Then presents the characteristics of his character in School Quilombola differential treatment, identified the actions teachers and community participation in the adequacy of the traditional curriculum. The research has the sources of the records of field research, interviews with leaders and questionnaires administered to teachers. As regards the theoretical approach, working with the concepts of quilombo communities, curriculum plural in its size, following Ivor Goodson, Michael Apple and Jean Claude Forquim. It relies on analysis of interviews in the relationship between memory and oral history